2013
DOI: 10.1093/ejcts/ezt560
|View full text |Cite
|
Sign up to set email alerts
|

Pedicled no-touch saphenous vein graft harvest limits vascular smooth muscle cell activation: the PATENT saphenous vein graft study†

Abstract: SVGs harvested using the 'NT' technique exhibit an early molecular and morphological pattern consistent with decreased VSMC activation compared with CON harvesting. Functional leg recovery was similar in both groups at 12 months. Larger studies are required to corroborate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
94
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 23 publications
3
94
3
Order By: Relevance
“…This procedure involves harvesting a SV with the perivascular tissue intact without direct contact or manipulation of the vein long-term improvement. 33) The morphological characteristics of the vein, such as the luminal diameter, 31) the collagen in the tunica adventitia, 32) the circular distribution pattern of the smooth muscle cells in the tunica media, 31) and the endothelium in the tunica intima, remain intact. 32) The vasa vasorum and the expression of the nitric oxide synthase in the tunica intima increase, whereas the atherosclerotic process is reduced.…”
Section: Coronary Arteriesmentioning
confidence: 99%
See 4 more Smart Citations
“…This procedure involves harvesting a SV with the perivascular tissue intact without direct contact or manipulation of the vein long-term improvement. 33) The morphological characteristics of the vein, such as the luminal diameter, 31) the collagen in the tunica adventitia, 32) the circular distribution pattern of the smooth muscle cells in the tunica media, 31) and the endothelium in the tunica intima, remain intact. 32) The vasa vasorum and the expression of the nitric oxide synthase in the tunica intima increase, whereas the atherosclerotic process is reduced.…”
Section: Coronary Arteriesmentioning
confidence: 99%
“…9) Regarding the morphology of the SV, a Turkish study reported a mean length of 72.42 ± 6.60 cm. 20) The luminal diameter varies in proximal, medial, and distal segment itself, thus avoiding distension prior to anastomosis, 31,32) which can cause intimal and medial hyperplasia, leading to graft failure. 31) When using conventional or manual dilatation technique, the SV is often stripped of its adventitial layer and distended, causing damage to the wall.…”
Section: Coronary Arteriesmentioning
confidence: 99%
See 3 more Smart Citations